A synthesis of clinical and health system bottlenecks to implementing new WHO postpartum hemorrhage recommendations: Secondary data analysis of the Kenya Confidential Enquiry into Maternal Deaths 2014–2017. (28th June 2022) - Ameh, Charles A.; Meka, Ramya Jyothi; West, Florence; Dickinson, Fiona; Allott, Helen; Godia, Pamela
Abstract: Objective: To describe maternal deaths from postpartum hemorrhage (PPH) in Kenya by secondary analysis of the Kenya Confidential Enquiry into Maternal Deaths (CEMD) database and clinical audit of a sample of those deaths, and to identify the perceived challenges to implementing country‐specific PPH guidelines. Methods: A retrospective descriptive study using the Kenyan CEMD database and anonymized maternal death records from 2014–2017. Eight standards from the Kenya National Guidelines for Quality Obstetric and Perinatal Care were selected to perform clinical audit. The process of supporting eight Sub‐Saharan African countries to develop country‐specific PPH guidelines was described and perceived challenges implementing these were identified. Results: In total, 725 women died from PPH. Most women attended at least one antenatal care visit (67.2%) and most did not receive iron and folate supplementation (35.7%). Only 39.0% of women received prophylactic uterotonics in the third stage of labor. Factors significantly associated with receiving prophylactic uterotonics were place of delivery (χ 2  = 43.666, df = 4; P  < 0.001), being reviewed by a medical doctor (χ 2  = 16.905, df = 1; P  < 0.001), and being reviewed by a specialist (χ 2  = 49.244, df = 1; P  < 0.001). Only three of eight standards had a greater percentage of met cases in comparison to unmet cases. Key concerns about implementation of the new WHO PPH guidance included use of misoprostol by unskilled health personnel, availability of misoprostol and tranexamic acid (TXA) at primary healthcare level, lack of availability of heat‐stable carbetocin (HSC) due to cost, lack of awareness and education about HSC and TXA, and lack of systems to ensure quality oxytocin is available at point of care. Conclusion: There is a need for improved quality of care for women to minimize the risk of mortality from PPH, by implementing updated clinical guidelines combined with focused health system interventions. Synopsis: Improving quality of care for women with postpartum hemorrhage requires use of up‐to‐date clinical guidelines combined with focused health system interventions.